Synapsin-Dependent Vesicle Recruitment Modulated by Forskolin, Phorbol Ester and Ca2+ in Mouse Excitatory Hippocampal Synapses - Hvalby, Øivind; Jensen, Vidar; Kao, Hung-Teh; Walaas, Sven I. (Frontiers in Synaptic Neuroscience, 2010)
Repeated release of transmitter from presynaptic elements depends on stimulus-induced Ca2+ influx together with recruitment and priming of synaptic vesicles from different vesicle pools. We have compared three different manipulations of synaptic strength, all of which are known to increase short-term synaptic efficacy through presynaptic mechanisms, in the glutamatergic CA3-to-CA1 stratum radiatum synapse in the mouse hippocampal slice preparation. Synaptic responses elicited from the readily releasable vesicle pool during low-frequency synaptic activation (0.1 Hz) were significantly enhanced by both the adenylate cyclase activator forskolin, the priming activator β-phorbol-12,13-dibutyrate (PDBu) and 4 mM [Ca2+]o, whereas during 20 Hz stimulation, the same manipulations reduced the time needed to reach the peak and increased the magnitude of the resulting frequency facilitation. In contrast, paired-pulse facilitations were unchanged in the presence of forskolin, decreased by 4 mM [Ca2+]o and essentially abolished by PDBu. The subsequent delayed response enhancement (DRE) responses, elicited during continuous 20 Hz stimulations and mediated by recruited vesicles, were enhanced by forskolin, essentially unchanged by PDBu and slightly decreased by 4 mM [Ca2+]o. Similar experiments done on slices devoid of the vesicle-associated synapsin I and II proteins indicated that synapsin I/II-induced enhancements of vesicle recruitment were restricted to Ca2+-induced frequency facilitations and forskolin-induced enhancements of the early DRE phase, whereas the proteins had minor effects during PDBu-treatment and represented constraints on late Ca2+- induced responses. The data indicate that in these glutamatergic synapses, the comparable enhancements of single synaptic responses induced by these biochemical mechanisms can be transformed during prolonged synaptic stimulation into highly distinct short-term plasticity patterns, which are partly dependent on synapsins I/II.